Blood Pressure Variability is Better Associated with Acute Relative Hyperglycemia Than the Heart Rate Variability in Healthy Young Adults - Prakash, Kiran; Ranjan, Navkiran; Malhotra, Anita S. (Experimental and Clinical Endocrinology & Diabetes, 2024)
Background Deranged cardiovascular autonomic functions are well-reported complications of diabetes mellitus, where chronic hyperglycemia is an important factor. The role of acute relative hyperglycemia on cardiovascular autonomic functions, particularly on blood pressure variability in healthy subjects, has been rarely explored. Therefore, this study aimed to examine the effect of acute relative hyperglycemia on cardiovascular autonomic functions in healthy young adults.Methods Beat-to-beat blood pressure and electrocardiogram were recorded to assess the heart rate variability and blood pressure variability in 42 young, healthy subjects during fasting and relative hyperglycemic states. Recorded cardiovascular parameters were analyzed in time and frequency domains. Correlations among analyzed parameters of cardiovascular autonomic variabilities were explored during fasting and relative hyperglycemic state.Results A few of the systolic, mean, and diastolic blood-pressure-variability parameters were significantly altered during acute relative hyperglycemia when compared to the fasting state. However, no significant changes were observed in any of the heart-rate-variability parameters. Also, novel significant correlations were found among many of the parameters of cardiovascular autonomic variabilities during fasting and relative hyperglycemic states.Conclusions The blood pressure variability is affected significantly during acute relative hyperglycemia in healthy young adults; however, the heart rate variability does not show such changes. Also, many blood pressure variability parameters show significant correlations with heart rate variability and baroreflex sensitivity. It may be hypothesized that although the variabilities in heart rate and blood pressure assess cardiovascular autonomic functions, blood pressure variability is a better indicator of cardiovascular autonomic effects of acute relative hyperglycemia.
Keywords: beat-to-beat blood pressure; electrocardiogram; hyperglycemia; autonomic